Aerosol and splatter generation with rotary handpieces used in restorative and orthodontic dentistry: a systematic review - Waraf Al-yaseen; Rhiannon Jones; Scott McGregor; William Wade; Jennifer Gallagher; Rebecca Harris; Ilona Johnson; Sukriti KC; Mark Robertson; Nicola Innes (Nature Publishing Group, 2022)
Abstract Introduction The COVID-19 pandemic has caused major disruptions in dental care globally, in part due to the potential for contaminated aerosol to be generated by dental activities. This systematic review assesses the literature for changes in aerosol-contamination levels when rotary instruments are used, (1) as distance increases from patient's mouth; (2) as time passes after the procedure; and (3) when using different types of handpieces. Methods The review methods and reporting are in line with PRISMA statements. A structured search was conducted over five platforms (September 2021). Studies were assessed independently by two reviewers. To be eligible studies had to assess changes in levels of aerosol contamination over different distances, and time points, with rotary hand instruments. Studies' methodologies and the sensitivity of the contamination-measurement approaches were evaluated. Results are presented descriptively. Results From 422 papers identified, 23 studies were eligible. All investigated restorative procedures using rotary instruments and one study additionally looked at orthodontic bracket adhesive material removal. The results suggest contamination is significantly reduced over time and distance. However, for almost all studies that investigated these two factors, the sizes of the contaminated particles were not considered, and there were inconclusive findings regarding whether electric-driven handpieces generate lower levels of contaminated particles. Conclusion Aerosol contamination levels reduce as distances, and post-procedure times increase. However, there was sparce and inconsistent evidence on the clearing time and no conclusions could be drawn. High-speed handpieces produce significantly higher levels of contamination than slow-speed ones, and to a lesser extent, micro-motor handpieces. However, when micro-motor handpieces were used with water, the contamination levels rose and were similar to high-speed handpiece contamination levels.